Contraceptive use and associated factors among women with HIV receiving care at a faith-based tertiary hospital in Northern Uganda: a cross-sectional study - Judith P. Acayo; Simon Peter Oryema; Robert Edilu; Henry Ochola; Sande Ojara; Pebalo Francis Pebolo; Felix Bongomin; Raymond Otim; Harriet Akello; Emmanuel Ochola (Therapeutic Advances in Reproductive Health, 2025)
Background: Preventing unintended pregnancies among reproductive-aged women with HIV (WWH) is crucial in combating mother-to-child transmission (MTCT) of HIV. We assessed the utilization of modern contraceptives and related factors among WWH attending the antiretroviral therapy (ART) clinic at a faith-based tertiary hospital in northern Uganda. Objectives: To determine the proportion of and factors associated with the utilization of modern contraceptives among WWH of reproductive age attending the ART clinic in St. Mary’s Hospital Lacor. Design: This cross-sectional study was conducted at the HIV clinic within St. Mary’s Hospital Lacor, from February to May 2023. Methods: Between February and May 2023, we conducted a cross-sectional study among randomly selected WWH of reproductive age attending the ART clinic at a faith-based health facility, St. Mary’s Hospital Lacor in Gulu city, northern Uganda. Quantitative data were collected using semi-structured questionnaires and analyzed using STATA version 16. Factors associated with the utilization of modern contraceptives were assessed using multivariable logistic regression. p  < 0.05 was considered statistically significant. Results: Of the 385 enrolled participants, 94 (24.4%) reported current modern contraceptive use, and 58 (15.1%) were using natural methods. Being referred to another facility to access modern contraceptives (adjusted odds ratio (aOR): 2.60, 95% confidence interval (CI): 1.31–5.17, p  < 0.01), prior use of modern contraceptive (aOR: 32.47, 95% CI: 3.56–300.94, p  < 0.01), and age (aOR: 0.92, 95% CI: 0.87–0.98, p  < 0.01) were all statistically associated with uptake of modern contraceptives. Conclusion: Only about one in every four WWH was currently using modern methods of contraceptives. There is a need to provide regular counseling to WWH on modern contraceptive methods to create awareness of the vital connection between modern contraceptive use and MTCT, as well as strengthen referral of clients opting to use modern contraceptives to facilities providing these services.